Preparation and biological activity application of hexagonal copper sulfide

Through the use of hexagonal copper sulfide nanosheets, the shortcomings of existing nanomaterials in antibacterial effects are solved, and methods to effectively inhibit methicillin-resistant Staphylococcus aureus are achieved, with deeper tissue penetration and good biosafety , suitable for the treatment of drug-resistant bacteria and infection inhibition.

CN119258092APending Publication Date: 2025-01-07WENZHOU MEDICAL UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310479915.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-04-28
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

In terms of antibacterial effects, existing nanomaterials have problems such as poor interaction between bacteria and antibacterial agents, low electron transfer efficiency and low photothermal efficiency, and it is particularly difficult to effectively inhibit the infection of methicillin-resistant Staphylococcus aureus.

Method used

Hexagonal copper sulfide nanosheets are used as catalysts, which have peroxidase-like activity, and can efficiently catalyze low-concentration hydrogen peroxide to produce hydroxyl radicals under near-infrared light irradiation, improve the photothermal conversion efficiency, and be used to prepare drug-resistant bacteria inhibitors , biofilm inhibitors and therapeutic agents for subcutaneous infection abscess.

Benefits of technology

Deeper tissue penetration and synergistic mild antibacterial effects are achieved, effectively inhibiting methicillin-resistant Staphylococcus aureus, reducing thermal damage to normal tissues, and showing good biosafety and antibacterial properties in and out of the body.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119258092A_ABST
    Figure CN119258092A_ABST
Patent Text Reader

Abstract

The invention discloses an application of a hexagonal copper sulfide nano-platform with photo-thermal enhanced peroxidase activity in treatment of methicillin-resistant staphylococcus aureus infection so as to promote healing of infected wounds. An improved one-pot method is adopted to synthesize a hexagonal copper sulfide nano-sheet. Due to the fact that the hexagonal copper sulfide nanosheet shows good photothermal conversion efficiency and photothermal stability in a second near-infrared window and further shows excellent peroxidase-like activity, temperature rise caused by the photothermal effect of the hexagonal copper sulfide nanosheet remarkably amplifies the peroxidase-like activity of the hexagonal copper sulfide nanosheet. The hexagonal copper sulfide nanosheet plays a good biological catalytic antibacterial role in vitro, under photo-thermal irradiation, abscess fading and healing of in-vivo methicillin-resistant staphylococcus aureus infected wounds are promoted, and toxicity can be ignored. The copper sulfide nanosheet provides a feasible strategy for effectively treating a deep methicillin-resistant staphylococcus aureus infected wound by utilizing a synergistic treatment platform.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of antibacterial biological activity, in particular to a study on the inhibitory effect of a copper-based nanomaterial catalyst on methicillin-resistant Staphylococcus aureus, and specifically to a synthesis method and application of hexagonal copper sulfide nanosheets. Background Art

[0002] Staphylococcus aureus can cause a variety of infections while developing resistance to traditional antibiotics. In particular, methicillin-resistant Staphylococcus aureus is the most common cause of skin and soft tissue infections, osteomyelitis, and bacteremia. In addition, these bacteria are extremely resistant to conventional antibiotics due to acquired drug resistance. Nanozymes are considered to be promising nanomaterials that can kill bacteria through in situ generated reactive oxygen species (ROS). ROS are oxygen-containing reactive molecules, including singlet oxygen, hydroxyl radicals, superoxide anion radicals, and hydrogen peroxide. The mechanism of ROS generation mainly involves peroxidase-like (POD) activity, and low concentrations of hydrogen peroxide are catalyzed to generate highly toxic hydroxyl radicals to eliminate bacteria and biofilms. Unlike traditional antibiotics, ROS can effectively kill bacteria without developing drug resistance.

[0003] Driven by nanotechnology, multifunctional nanomaterials such as silver nanoparticles, carbon-based nanoparticles, gold nanoparticles, and zinc- and copper-based nanoparticles have been explored as tools to kill pathogenic microorganisms. Compared with the above nanomaterials, copper-based nanoparticles have the advantages of low cost, simple preparation, high stability, and good biocompatibility, and have become new nanomaterials in the fields of electronics, optics, catalysis, and biomedicine. Copper ions are necessary catalysts for many enzymes, proteins, and transcription factors to properly maintain their functions and play an important role in many wound healing processes.

[0004] Although many nanomaterials have been produced, many of these nanomaterials suffer from poor bacteria-antimicrobial interactions, low electron transfer efficiency, and low photothermal efficiency. Summary of the invention

[0005] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a preparation and biologically active application of a hexagonal copper sulfide nanosheet catalyst with deeper tissue penetration and synergistic mild antibacterial properties.

[0006] To achieve the above-mentioned purpose, the present invention provides a hexagonal copper sulfide nanosheet, which belongs to the field of antibacterial copper-based nanomaterial catalysts, has peroxidase-like activity, can locally catalyze low-concentration hydrogen peroxide and produce hydroxyl radicals, and can exhibit high photothermal conversion efficiency and photothermal stability under near-infrared light irradiation.

[0007] The present invention provides the application of the above-mentioned hexagonal copper sulfide nanosheets, and the hexagonal copper sulfide nanosheets are used for preparing drug-resistant bacteria inhibitors, drug-resistant bacteria biofilm inhibitors and subcutaneous drug-resistant bacteria infection abscess therapeutic agents.

[0008] In a specific embodiment of the present invention, the drug-resistant bacteria inhibitor is a methicillin-resistant Staphylococcus aureus lysis inhibitor.

[0009] In a specific embodiment of the present invention, the drug-resistant bacteria biofilm inhibitor is a methicillin-resistant Staphylococcus aureus biofilm inhibitor.

[0010] In a specific embodiment of the present invention, the therapeutic agent for subcutaneous abscess infection caused by drug-resistant bacteria is a therapeutic agent for subcutaneous abscess infection caused by methicillin-resistant Staphylococcus aureus.

[0011] In a specific embodiment of the present invention, the drug-resistant bacteria inhibitor is a photothermal amplified peroxidase methicillin-resistant Staphylococcus aureus inhibitor.

[0012] Preferably, hexagonal copper sulfide nanosheets combined with NIR photothermal combination system are used to prepare drug-resistant bacteria inhibitors, drug-resistant bacteria biofilm inhibitors and subcutaneous drug-resistant bacteria infection abscess therapeutic agents.

[0013] Preferably, the drug-resistant bacteria inhibitor and the therapeutic agent are irradiated with a 1270 nm laser with an intensity of 1 W cm -2 Conditions: effective concentration is 100 μg / mL, time is 5 minutes,

[0014] Preferably, hexagonal copper sulfide nanosheets are combined with H2O2 to prepare drug-resistant bacteria inhibitors, drug-resistant bacteria biofilm inhibitors and subcutaneous drug-resistant bacteria infection abscess therapeutic agents.

[0015] Preferably, the concentration of hydrogen peroxide is 0.1 mmol.

[0016] Preferably, the single-layer Mo4VC4 nanosheet is combined with H2O2 and NIR photothermal combination system to prepare drug-resistant bacteria inhibitors, drug-resistant bacteria biofilm inhibitors and subcutaneous drug-resistant bacteria infection abscess therapeutic agents.

[0017] Furthermore, the resistant bacteria inhibitors and therapeutic agents were irradiated with 1270 nm laser at an intensity of 1 W cm -2 The conditions used were: effective concentration of 100 μg / mL, time of 5 minutes, and hydrogen peroxide concentration of 0.1 mmol.

[0018] The present invention also provides an antibacterial drug composition, which comprises hexagonal copper sulfide nanosheets and H2O2.

[0019] The present invention also provides a synergistic nano antibacterial combination system of copper-based nanomaterials combined with near-infrared light and heat, comprising hexagonal copper sulfide nanosheets and near-infrared lasers.

[0020] Further, it includes hexagonal copper sulfide nanosheets, H2O2 and near-infrared lasers.

[0021] Furthermore, under 1270 nm laser irradiation, the intensity is 1 W cm -2 The conditions used were, the effective concentration of hexagonal copper sulfide nanosheets was 100 μg / mL, the time was 5 min, and the H2O2 concentration was 0.1 mmol.

[0022] The present invention also provides a method for preparing hexagonal copper sulfide nanosheets, comprising the following steps:

[0023] Step 1, mixing copper acetate and oleylamine, evacuating the mixture, and heating to dissolve the mixture to obtain a copper acetate solution;

[0024] Step 2: The mixed solution of sulfur and oleylamine is vacuum degassed and purged with nitrogen, and sulfur and the copper acetate solution prepared in step 1 are added by injection at 100-200°C;

[0025] Step 3: After cooling, dilute the reaction mixture prepared in step 2 with toluene;

[0026] Step 4: Wash the product prepared in step 3 by adding a methanol / acetone mixture, centrifuge and then resuspend the precipitate in toluene for washing.

[0027] Preferably, the concentration of copper acetate in the copper acetate solution in step 1 is 5-100 mmol / L.

[0028] Preferably, the syringe gradually adds 0.02-0.08M copper acetate solution and 0.2M sulfur solution as precursors at a rate of 0.04-0.085mL / min.

[0029] The present invention has the following advantages:

[0030] The hexagonal copper sulfide nanoplatform based on copper-based nanomaterials has peroxidase-like catalytic activity, which can effectively overcome the problems of low tissue penetration and catalytic activity. Specifically, it has a unique two-dimensional planar structure, a large specific surface area, a special crystal structure, and unique physical properties such as high hole concentration. It shows a very significant localized surface plasmon resonance (LSPR) absorption peak in the near-infrared region II (980-1350nm), and has good optical and electronic properties.

[0031] Relatively speaking, other copper sulfide nanoparticles have a wide absorption capacity from 700nm to 1100nm, cannot absorb long-term near-infrared light under deep tissues, and have low photothermal efficiency. In addition, a single photothermal therapy (>50℃) can kill bacteria but also cause damage to surrounding normal tissues.

[0032] Hexagonal copper sulfide nanosheets absorb light and heat in the near-infrared II region, thereby improving their photothermal conversion efficiency, and are more suitable for in vivo applications with higher skin tolerance thresholds and have deeper tissue penetration.

[0033] In addition, its peroxidase-like activity achieves efficient photothermal amplification, which can be used to treat methicillin-resistant Staphylococcus aureus infections, further avoiding thermal damage to normal tissues. The biosafety and antibacterial properties of the hexagonal copper sulfide nanoplatform were systematically evaluated in vivo and in vitro. This work provides a feasible strategy for the effective treatment of methicillin-resistant Staphylococcus aureus infected wounds, and also provides a reliable direction for the design and application of copper-based nanomaterial catalysts. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 A is a schematic diagram of the synthesis of hexagonal copper sulfide nanosheets in Example 1,

[0035] Figure 1 B is a transmission electron microscope image of hexagonal copper sulfide nanosheets in Example 2.

[0036] Figure 1 C is the selected area electron diffraction (SAED) image of hexagonal copper sulfide nanosheets.

[0037] Figure 1 D is a high-resolution TEM (HRTEM) image of hexagonal copper sulfide nanosheets.

[0038] Figure 1 E is the absorption spectrum of hexagonal copper sulfide nanosheets,

[0039] Figure 1 F is the dark field image of hexagonal copper sulfide nanosheets with uniform contrast.

[0040] Figure 1 G is the EDS element spectrum of Cu ions in hexagonal copper sulfide nanosheets.

[0041] Figure 1 H is the EDS elemental spectrum of S ions in hexagonal copper sulfide nanosheets,

[0042] Figure 1 I is the EDS element spectrum of hexagonal copper sulfide nanosheets,

[0043] Figure 1J is the energy dispersive X-ray (EDX) elemental mapping image of hexagonal copper sulfide nanosheets.

[0044] Figure 1 K is the X-ray photoelectron 2p nuclear energy level spectrum,

[0045] Figure 1 L is the X-ray photoelectron 2p nuclear energy level spectrum corresponding to the Cu peak,

[0046] Figure 1 M is the X-ray photoelectron 2p nuclear energy level spectrum corresponding to the S peak;

[0047] Figure 2 A is the absorption spectrum of hexagonal copper sulfide nanosheets with different concentrations in Example 3,

[0048] Figure 2 B is a statistical chart showing the temperature changes of hexagonal copper sulfide nanosheet solutions with different concentrations irradiated by near-infrared light.

[0049] Figure 2 C is the thermal imaging diagram of the temperature change of hexagonal copper sulfide nanosheet solutions with different concentrations irradiated by near-infrared light.

[0050] Figure 2 D is the temperature curve of 100 μg / mL hexagonal copper sulfide nanosheets under five cycles of near-infrared radiation.

[0051] Figure 2 E is the result diagram of the photothermal conversion efficiency of hexagonal copper sulfide nanosheets.

[0052] Figure 2 F is the cooling time and -lnθ curve of hexagonal copper sulfide nanosheets,

[0053] Figure 2 G is the peroxidase catalytic model of hexagonal copper sulfide nanosheets.

[0054] Figure 2 H is the peroxidase catalytic activity of hexagonal copper sulfide nanosheets at different concentrations in Example 3,

[0055] Figure 2 I is the peroxidase catalytic activity of hexagonal copper sulfide nanosheets on TMB at different times in Example 3,

[0056] Figure 2 J is the peroxidase catalytic activity of hexagonal copper sulfide nanosheets on OPD at different times in Example 3,

[0057] Figure 2 K is the peroxidase catalytic activity of the hexagonal copper sulfide nanosheets to OPD under NIR-II conditions at different times in Example 3,

[0058] Figure 2 L is a statistical graph of the peroxidase catalytic activity results of hexagonal copper sulfide nanosheets on OPD in the presence and absence of NIR-II at different times in Example 3;

[0059] Figure 3 A is the effect of plate coating on Staphylococcus aureus in 8 experimental groups in Example 4,

[0060] Figure 3 B is the statistical result of the effect of plate coating on Staphylococcus aureus in 8 experimental groups in Example 4,

[0061] Figure 3 C is the live / dead staining analysis of bacteria on plates of 8 experimental groups in Example 4,

[0062] Figure 3 D is the statistical result of the bacterial fluorescence quantitative analysis after the live / dead staining of bacteria on the plates of the 8 experimental groups in Example 4,

[0063] Figure 3 E is the morphological experiment of 8 experimental groups on plate coating against Staphylococcus aureus in Example 4,

[0064] Figure 3 F is the experiment of removing Staphylococcus aureus biofilm in 8 experimental groups in Example 4,

[0065] Figure 3 G is a statistical graph of the amount of Staphylococcus aureus biofilm after treatment in 8 experimental groups in Example 4,

[0066] Figure 3 H is the fluorescence image of live / dead bacteria staining of Staphylococcus aureus biofilm after treatment in 8 experimental groups in Example 4;

[0067] Figure 4 A is the flow chart for establishing the mouse subcutaneous abscess model.

[0068] Figure 4 B is the temperature of the abscess of mice after treatment in the experimental groups of PBS+NIR-II, CuS NSs+NIR-II, and CuS NSs+H2O2+NIR-II in Example 5,

[0069] Figure 4 C is a photo of subcutaneous abscesses in mice after treatment in the four experimental groups in Example 5.

[0070] Figure 4 D is an enlarged image of the subcutaneous abscess of mice after treatment in the four experimental groups in Example 5.

[0071] Figure 4 E: Plate colony images of bacteria in subcutaneous abscesses of each group of mice;

[0072] Figure 4 Statistical results of infection area related to subcutaneous abscess in F mice,

[0073] Figure 4 G is the statistical result of colony counting of skin tissue collected from subcutaneous abscesses of mice.

[0075] Figure 4 H is the H&E staining result of the subcutaneous wound tissue of mice in the four experimental groups on the 10th day after treatment.

[0076] Figure 4 J is the statistical diagram of H&E staining absorbance intensity of subcutaneous wound tissue of mice on the 10th day after treatment in the four experimental groups.

[0077] Figure 4 I is the Masson staining result of the subcutaneous wound tissue of mice on the 10th day after treatment in the four experimental groups.

[0078] Figure 4 K is a statistical graph of collagen deposition in the subcutaneous wound tissue of mice on the 10th day after treatment in the four experimental groups;

[0079] Figure 5 A is the result of the red blood cell distribution width (RDW) in the blood routine test of mice after being treated with hexagonal copper sulfide nanosheets in Example 6,

[0080] Figure 5 B is the result graph of mean corpuscular hemoglobin concentration (MCHC).

[0081] Figure 5 C is the platelet count (PLT) result chart.

[0082] Figure 5 D is the white blood cell (WBC) result chart.

[0083] Figure 5 E is the result diagram of hemoglobin (HGB),

[0084] Figure 5 F is the result of hematocrit (HCT).

[0085] Figure 5 G Mean Corpuscular Volume (MCV) result graph,

[0086] Figure 5 H is the result graph of red blood cells (RBC),

[0087] Figure 5 I is the mean platelet volume (MPV) result diagram,

[0088] Figure 5J is the mean corpuscular hemoglobin (MCH) result graph,

[0089] Figure 5 K is the result graph of transaminase (ALT),

[0090] Figure 5 L is the result graph of creatine kinase (CK),

[0091] Figure 5 M is the urea nitrogen (BUN) result diagram,

[0092] Figure 5 N is the result diagram of glutamyl transferase (GGT),

[0093] Figure 5 O is the result of aspartate aminotransferase (AST),

[0094] Figure 5 P is the effect of different concentrations of hexagonal copper sulfide nanosheets on the hemolysis rate. DETAILED DESCRIPTION

[0095] The present invention will be further described in detail below with reference to embodiments and effect examples, but the scope of the present invention is not limited thereto.

[0096] Example 1 Synthesis of hexagonal copper sulfide nanosheets

[0097] Mix 0.8 mmol of copper acetate and 20 mL of oleylamine, add to a 50-mL three-necked flask, stir vigorously, and degas in vacuo for 30 minutes. Then, fill the flask with nitrogen and gradually heat to dissolve to obtain a copper acetate solution.

[0098] Take a solution containing 2 mL of sulfur and 0.5 M oleylamine, degas it and purge it with nitrogen, heat it at 150°C, and gradually add 0.02-0.08 M copper acetate solution and 0.2 M sulfur solution at a rate of 0.04-0.085 mL / min.

[0099] After cooling to room temperature, the reaction mixture was diluted with toluene and the nanocrystals were purified. A methanol / acetone mixture was added and then centrifuged to precipitate it. The precipitate was resuspended in toluene and the washing process was repeated twice to obtain hexagonal copper sulfide nanosheets.

[0100] Example 2 Characterization of Hexagonal Copper Sulfide Nanosheets

[0101] Representative TEM images of hexagonal copper sulfide nanosheets are shown in Figure 2. Figure 1 B. As can be seen from the image, uniform hexagonal nanosheets with diameters ranging from 56.7 to 103.06 nm are essentially the only morphology. The hexagonal symmetric spots in the fast Fourier transform (FFT) pattern clearly indicate that the flakes are single crystals ( Figure 1C). High-resolution transmission electron microscopy (HRTEM) experiments show that the nanosheets have a relatively smooth surface. From the HRTEM image ( Figure 1 D), the measured lattice fringes are 0.19nm and 0.33nm, which are in good agreement with the (110) and (100) diffraction results of hexagonal CuS, verifying the successful synthesis of hexagonal copper sulfide nanosheets. The absorption spectrum of hexagonal copper sulfide nanosheets was measured by UV-visible-near infrared diffuse reflectance spectrophotometer, and its near-infrared absorption range is 650-1800nm ​​( Figure 1 E). The elemental distribution of the hexagonal copper sulfide nanosheets was determined by high-angle annular dark-field scanning transmission electron microscopy (HAADF-STEM) energy dispersive X-ray spectroscopy (EDS) elemental mapping analysis. The dark-field image of a single hexagonal copper sulfide nanosheet has uniform contrast ( Figure 1 F), and the corresponding EDS elemental map reveals the uniform distribution of Cu and S elements, indicating that no phase separation occurs during the growth of hexagonal copper sulfide nanosheets ( Figure 1 G-1I). The position and intensity of the diffraction peaks are well marked with the JCPDS card number, indicating that the product is a standard hexagonal copper sulfide. The three strong peaks with 2θ values ​​of 29.27°, 31.77° and 48.08° correspond to the three crystal planes (102), (103) and (110) of copper sulfide, respectively. No other impurity characteristic peaks were observed, indicating that the sample is of high purity. The broad diffraction peaks in the X-ray diffraction (XRD) pattern indicate that the size of the hexagonal copper sulfide nanosheets is very small ( Figure 1 J). XPS was used to characterize the sample and investigate its composition and purity. 2p nuclear energy level spectrum ( Figure 1 K) shows, Figure 1 The two peaks at 932.14 and 952.10 eV in L correspond to Cu 2p 3 / 2 and Cu2p 1 / 2 Binding energy, Figure 1 The two peaks at 162.15 and 163.2 eV or 168.9 eV in M ​​correspond to S2p 3 / 2 and S2p 1 / 2 The binding energy is consistent with the reported value. The results show that no obvious impurities were found on the surface of the product, indicating that the prepared hexagonal copper sulfide nanosheets are relatively pure.

[0102] Photothermal and nanozyme performance of hexagonal copper sulfide nanosheets in Example 3

[0103] The spectral characteristics of hexagonal copper sulfide nanosheets were determined by ultraviolet-visible-near infrared absorption spectroscopy (UV-vis-NIR). The absorption range of hexagonal copper sulfide nanosheets under UV-vis-NIR for laser energy in the near-infrared region 1 and near-infrared region 2 is very wide, and is proportional to the increase in the concentration of the hexagonal copper sulfide nanosheet dispersion. This shows that the photothermal agent has good potential in photothermal therapy ( Figure 2 A). In order to study its photothermal properties, different concentrations (0, 50, 100, 200 μg mL -1 ) was exposed to near-infrared radiation (1270 nm, 1.0 W cm -2 ). When the concentration was increased from 50 μg mL -1 Gradually increase to 200 μg mL -1 When the temperature reached 43.2, 48.8 and 53°C in 6 minutes, the water temperature did not even reach 37°C. Figure 2 B). In addition, the photothermal performance of hexagonal copper sulfide nanosheets is positively correlated with the laser power density. When the 1270nm laser power density increases from 0.2W cm -2 Increased to 1.0W cm -2 When the hexagonal copper sulfide nanosheet dispersion (100 μg mL -1 ) After 6 minutes of laser irradiation, the temperatures increased by 36.6, 40.2, 44.1 and 48.8℃ respectively ( Figure 2 C). This result shows that under the irradiation of near-infrared light in the second region, hexagonal copper sulfide nanosheets exhibit good photothermal performance. In order to further evaluate the photothermal effect, the hexagonal copper sulfide nanosheets were exposed to near-infrared light in the second region (1270nm, 1.0W cm -2 , 6min) for 5 heating / cooling cycles, and the photothermal performance was stable throughout the cycle ( Figure 2 D). The heating / cooling curves show that the photothermal conversion efficiency (η) at 1270 nm is 44.1% ( Figure 2 E and 2F). These results suggest that this desirable property of hexagonal copper sulfide nanosheets can be used for photothermal therapy to significantly convert light into heat.

[0104] TMB and OPD were used as substrates to evaluate the peroxidase activity of CuS NSs. Figure 2 G). Figure 2 As shown in Figure 3, in the presence of CuS NSs, with the addition of H2O2, a new TMB signal peak appeared at 652 nm. This indicates that TMB was oxidized to form oxTMB. When the concentration of CuS NSs was increased (0-200 μg mL -1 )( Figure 2 H) and increasing reaction time (0-30 min) ( Figure 2 I), the absorbance of TMB at 652 nm showed an increasing dependence. At the same time, CuS NSs showed the ability to oxidize OPD, generating a new absorption peak at 424 nm. The use of OPD probe showed similar effects as TMB ( Figure 2 J), providing evidence for the intrinsic peroxidase-like activity of CuS NSs. To further prove that NIR-II can increase the peroxidase-like activity of CuS NSs, the absorption of OPD at 424 nm in the presence and absence of NIR-II was studied. Figure 2 K and 2L show that the peroxidase activity of CuS NSs was significantly enhanced under NIR-II irradiation. These data indicate that CuS NSs have good peroxidase activity and NIR-II can significantly promote the peroxidase activity of CuS NSs.

[0105] In Example 4, hexagonal copper sulfide nanosheets inhibit the formation of methicillin-resistant Staphylococcus aureus and methicillin-resistant Staphylococcus aureus biofilm

[0106] Considering the photothermal and nanozyme properties of hexagonal copper sulfide (CuS NSs), the standard plate count method was used to further evaluate its antibacterial properties against methicillin-resistant Staphylococcus aureus. The experiment was divided into 8 groups. They were PBS group, CuS NSs group, H2O2 group, CuS NSs+H2O2 group, PBS+NIR-II group, CuS NSs+NIR-II group, H2O2+NIR-II group, and CuS NSs+H2O2+NIR-II group. The experimental group with NIR-II was exposed to near-infrared radiation in the second region (1270nm, 1.0W cm -2 , 6 min), the concentration of CuS NSs was 100 μg mL -1 , H2O2 concentration is 0.1mmol.

[0107] like Figure 3 As shown in A, there was a small reduction in colonies in the CuS NSs group, which may be related to the ultra-thin sheet structure, which can achieve a certain degree of antibacterial effect. In the CuS NSs+H2O2 group, the relative bacterial activity of MRSA decreased to 31.2%, indicating that CuSNSs can decompose H2O2 to generate hydroxyl radicals sufficient to kill bacteria. At the same time, the CuS NSs+NIR-II group showed a certain antibacterial activity, and the MRSA bacterial activity decreased to 48.6%. These results show that CuS NSs has a broad-spectrum antibacterial activity and that photothermal or catalytic effects alone cannot completely kill bacteria. The bacterial activity of the CuS NSs+H2O2+NIR-II group was significantly reduced, and the bactericidal rate of MRSA was 99.5% ( Figure 3B). This confirms that the material enhances nanozyme activity via NIR-II-enhanced peroxidation and can achieve complete bacterial eradication at lower concentrations.

[0108] Subsequently, bacterial live / dead staining analysis ( Figure 3 C) and bacterial fluorescence quantitative analysis ( Figure 3 D) It was confirmed that NIR-II irradiation can amplify the peroxidase-like activity of CuS NSs and achieve efficient bactericidal effects.

[0109] In the NIR+H2O2 sterilization system, the changes of MRSA were observed by scanning electron microscopy, which further proved the sterilization mechanism of CuS NSs. Figure 3 As shown in E, the bacterial morphology after PBS and H2O2 treatment was basically intact. The bacteria in the CuS NSs+NIR-II group and the CuSNSs+H2O2 group showed varying degrees of damage, and lesions and holes were visible in the bacterial cell wall and cell membrane. Especially in the CuS NSs+H2O2+NIR-II group, the bacterial structure was destroyed and the contents were released. This confirms that under NIR-II, CuS NSs converts H2O2 into lethal hydroxyl radicals. These data indicate that CuS NSs nanozymes can inhibit bacteria through the synergistic effects of photothermal and catalytic effects.

[0110] Biofilms consist of complex polymers outside bacterial cells that protect bacteria from host immune cells and resist the penetration of antibiotics or antimicrobial drugs. Therefore, inhibiting and destroying bacterial biofilms is essential to combat infection. Methicillin-resistant Staphylococcus aureus biofilms were analyzed by crystal violet staining, and the relative biofilm clearance after different treatments was evaluated. The more residual biofilm, the darker the purple color displayed. Figure 3 As shown in F and 3G, the purple color of the CuS NSs+NIR-II group and the CuS NSs+H2O2 group both became lighter to a certain extent, and the purple color of the CuS NSs+H2O2+NIR-II group was the lightest. 590 The nm value was the lowest, indicating that the treatment was effective in eliminating biofilm.

[0111] To further confirm the antibacterial potential of CuS NSs, we observed the outer membrane of bacteria using confocal microscopy. SYTO-9 and propidium iodide (PI) were used for live / dead bacteria staining. Green fluorescence represents live bacteria stained with SYTO-9, and red fluorescence represents dead bacteria stained with PI. Figure 3 As shown in Figure 3, compared with the PBS group, some red fluorescent spots appeared in the biofilms of the CuS NSs+NIR-II group and the CuS NSs+H2O2 group, and strong red fluorescent spots appeared in the biofilm of the CuS NSs+H2O2+NIR-II group, indicating that this anti-biofilm strategy can effectively eliminate bacterial biofilms.

[0112] Example 5 Hexagonal copper sulfide nanosheets inhibit bacterial growth and promote wound repair in mice

[0113] Encouraged by the above in vitro antibacterial properties, we further evaluated the in vivo anti-infection treatment of CuS NSs.

[0114] A subcutaneous abscess model was established on the back of mice. The experimental process was as follows: Figure 4 As shown in A.

[0115] The experiment was divided into 4 groups. They were PBS+NIR-II group, CuS NSs+NIR-II group, CuS NSs+H2O2 group, and CuS NSs+H2O2+NIR-II group. CuS NSs and / or H2O2 were subcutaneously injected into the infection site. The concentration of CuS NSs was 100 μg mL -1 , H2O2 concentration was 0.1mmol. The NIR-II irradiation group was exposed to near infrared II radiation (1270nm, 1.0W cm -2 , 5min).

[0116] Use a thermal imager to monitor the temperature changes of the infected area in real time. Figure 4 As shown in B, the temperature of the CuS NSs+NIR-II group and the CuS NSs+H2O2+NIR-II group increased to 48°C after 5 minutes, which was much higher than that of the control group (PBS+NIR-II). This indicates that CuS NSs exhibits good photothermal conversion efficiency in deep tissue infection.

[0117] The effectiveness of treatment is then assessed by monitoring changes in the wound area. Figure 4 As shown in C, during the wound healing process, obvious abscesses appeared on the wounds of the PBS group between days 0 and 3, indicating the presence of a large number of bacteria and a strong inflammatory response. In the CuS NSs+H2O2+NIR-II group, obvious scars appeared in the wounds, indicating a decrease in the number of bacteria and a process of repair reaction, which was reflected in the plate counts of bacteria in the subcutaneous abscesses of each group ( Figure 4 E and 4G). The wound size in the CuS NSs+H2O2+NIR-II group was significantly reduced by about 5.9%, while the wound sizes in the PBS+NIR-II, CuS NSs+NIR-II, and CuS NSs+H2O2 groups were 34.5%, 19.4%, and 14.9%, respectively. Figure 4 D and 4F), indicating that this synergistic treatment strategy can effectively promote abscess healing.

[0118] Tissue sections: Take the wound skin of the bacterial infection wound 10 days after treatment for hematoxylin-eosin staining (H&Estaining) and Masson staining (Masson staining), and take pictures under a microscope for observation. Figure 4 H and J show that the CuS NSs+NIR-II group, CuS NSs+H2O2 group, and CuS NSs+H2O2+NIR-II group can promote more complete epithelial formation in bacterially infected wounds. Compared with the control group, the treated group has a higher degree of granulation tissue, less bacterial distribution and inflammatory cells. In contrast, the control group has a large area of ​​scattered bacteria and inflammatory cells, indicating that the infection is not under control. Figure 4 As shown in I and K, the collagen fibers in the CuS NSs+NIR-II group, CuS NSs+H2O2, and CuS NSs+H2O2+NIR-II group were aggregated and arranged tightly. After 10 days of treatment, different amounts of collagen deposition appeared in each group, and the amount of collagen deposition in the CuS NSs+H2O2+NIR-II group increased further. After 10 days of treatment, the collagen deposition in the CuS NSs+H2O2+NIR-II group was more dense and similar to healthy skin. Quantitative data analysis showed that the wounds treated with the CuS NSs+H2O2+NIR-II group had the highest collagen density of about 99.76%, the collagen density of the wounds treated with the CuS NSs+NIR-II group was about: 46.1%, the collagen density of the wounds treated with the CuS NSs+H2O2 group was about: 46.4%, and the PBS+NIR-II control group was only 14.7%.

[0119] Biosafety Evaluation of Hexagonal Copper Sulfide Nanosheets in Example 6

[0120] In order to further study the biosafety of hexagonal copper sulfide nanosheets in future applications, we conducted hemolysis tests and blood analysis to prove the biosafety of hexagonal copper sulfide nanosheets.

[0121] Hemolysis experiments showed that even at 400 μg mL -1 No obvious hemolysis was found under the dose, which confirmed that the hexagonal copper sulfide nanosheets have good blood compatibility ( Figure 5 P). Figure 5As shown in A-5O, routine blood analysis, including red blood cell distribution width (RDW), mean corpuscular hemoglobin concentration (MCHC), platelet count (PLT), white blood cell (WBC), hemoglobin (HGB), hematocrit (HCT), mean corpuscular volume (MCV), red blood cell (RBC), mean platelet volume (MPV), and mean corpuscular hemoglobin (MCH) analysis, showed no obvious abnormalities. In addition, blood biochemical indicators transaminase (ALT), creatine kinase (CK), urea nitrogen (BUN), glutamyl transferase (GGT), and aspartate aminotransferase (AST) did not show obvious blood toxicity. The above results show that hexagonal copper sulfide nanosheets have good biocompatibility and potential clinical application value.

[0122] In summary, the present invention provides an enzyme-mimicking preparation based on hexagonal copper sulfide nanomaterials. The material has good peroxidase-mimicking activity and can be used to prepare enzyme-mimicking preparations with high catalytic activity. The material not only has good antibacterial activity against drug-resistant Staphylococcus aureus in vitro, but can also effectively kill Staphylococcus aureus in vivo and promote the healing of skin wounds of animals infected with Staphylococcus aureus; in the presence of low concentrations of H2O2, the enzyme-mimicking preparation based on hexagonal copper sulfide nanomaterials of the present invention has excellent in vivo antibacterial activity against Staphylococcus aureus and can accelerate wound healing. The hexagonal copper sulfide nanomaterial provided by the present invention is a non-antibiotic material and has excellent biocompatibility. It can solve the problem of bacterial resistance caused by the abuse of antibiotics and has broad application prospects in the preparation of bionic materials and antibacterial drugs.

[0123] The above content is a further detailed description of the present invention in combination with specific preferred implementation methods, and it cannot be determined that the specific implementation of the present invention is limited to these descriptions. For ordinary technicians in the technical field to which the present invention belongs, without departing from the concept of the present invention, its architecture can be flexible and can derive a series of products. Just making a few simple deductions or substitutions should be regarded as belonging to the scope of patent protection of the present invention determined by the submitted claims.

Claims

1. An application of hexagonal copper sulfide nanosheets, characterized in that: The hexagonal copper sulfide nanosheets are used for preparing drug-resistant bacteria inhibitors.

2. The use of a hexagonal copper sulfide nanosheet according to claim 1, characterized in that , the drug-resistant bacteria inhibitor is a methicillin-resistant Staphylococcus aureus inhibitor.

3. The use of a hexagonal copper sulfide nanosheet according to claim 1, characterized in that , the drug-resistant bacteria inhibitor is a drug-resistant bacteria biofilm inhibitor; Or the drug-resistant bacteria inhibitor is a therapeutic agent for abscesses infected with drug-resistant bacteria.

4. The use of any one of claims 1 to 3, characterized in that: Application of the hexagonal copper sulfide nanosheets combined with the NIR photothermal combination system in the preparation of drug-resistant bacteria inhibitors; or application of the hexagonal copper sulfide nanosheets combined with H2O2 in the preparation of drug-resistant bacteria inhibitors; Or the use of the hexagonal copper sulfide nanosheets combined with H2O2 and NIR photothermal combination system in the preparation of drug-resistant bacteria inhibitors.

5. An application of hexagonal copper sulfide nanosheets, characterized in that: The hexagonal copper sulfide nanosheets are used for preparing peroxidase-like agents.

6. An antibacterial drug composition, characterized in that: The composition includes hexagonal copper sulfide nanosheets and H2O2.

7. A synergistic nano antibacterial combination system of copper-based nanomaterials and near-infrared photothermal therapy, characterized in that: Including hexagonal copper sulfide nanosheets and near-infrared lasers.

8. The MXene combined with near-infrared photothermal synergistic nano-antibacterial combination system according to claim 7, characterized in that: Including hexagonal copper sulfide nanosheets, H2O2 and near-infrared lasers.

9. The MXene combined with near-infrared photothermal synergistic nano antibacterial combination system according to claim 8, characterized in that: Under 1270nm laser irradiation, the intensity is 0.6-2Wcm -2 The conditions used were as follows: the effective concentration of hexagonal copper sulfide nanosheets was 50-400 μg / mL, the time was 4-6 minutes, and the H2O2 concentration was 0.1 mmol.

10. A method for preparing hexagonal copper sulfide nanosheets, characterized in that: The steps include: Step 1, mixing copper acetate and oleylamine, evacuating the mixture, and heating to dissolve the mixture to obtain a copper acetate solution; Step 2: The mixed solution of sulfur and oleylamine is vacuum degassed and purged with nitrogen, and sulfur and the copper acetate solution prepared in step 1 are added by injection at 100-200°C; Step 3: After cooling, dilute the reaction mixture prepared in step 2 with toluene; Step 4: Wash the product prepared in step 3 by adding a methanol / acetone mixture, centrifuge and then resuspend the precipitate in toluene for washing.